Study on the effectiveness of reservoir length in improving electromigration in Cu/Low-k interconnects - Fu, Chunmiao (2011)
Electromigration (EM) occurs in the form of void formation because of mass transport, reducing the electrical reliability of interconnects. The aggressive shrinkage of interconnects while maintaining at high current capability and reliability emerges EM to be a serious reliability issue, especially with the introduction of Cu and low-k dielectric material in the backend integrated circuits. Reservoir region can contribute better EM reliability of interconnects. However, the effectiveness of the reservoir effect in improving EM reliability as a function of line width has not been studied. In this work, experimental studies on the reservoir effect of EM reliability are performed for the Cu/low-k dual-damascene interconnects with varied reservoir lengths in both narrow and wide metal lines. Finite element simulation is applied to assist us in understanding the mechanism of reservoir effect effectiveness.